2009
DOI: 10.1890/08-1884.1
|View full text |Cite
|
Sign up to set email alerts
|

Access to mycorrhizal networks and roots of trees: importance for seedling survival and resource transfer

Abstract: Mycorrhizal networks (MNs) are fungal hyphae that connect roots of at least two plants. It has been suggested that these networks are ecologically relevant because they may facilitate interplant resource transfer and improve regeneration dynamics. This study investigated the effects of MNs on seedling survival, growth and physiological responses, interplant resource (carbon and nitrogen) transfer, and ectomycorrhizal (EM) fungal colonization of seedlings by trees in dry interior Douglas-fir (Pseudotsuga menzie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(151 citation statements)
references
References 65 publications
7
143
0
1
Order By: Relevance
“…Insights from agriculture have long suggested the use of facilitative legumes to ameliorate soil conditions (Bradshaw 1983, Wong 2003. More recent studies have shown mycorrhizal inoculation improves plant survival and growth (e.g., Requena et al 2001, Pineiro et al 2013 although in some systems it may be the presence of a mycorrhizal network (Simard and Durall 2004, Teste et al 2009, Booth and Hoeksema 2010, as opposed to the presence of certain mycorrhizas alone, that facilitates successful restoration.…”
Section: Restoring Species Composition Requires More Than Just Plantsmentioning
confidence: 99%
“…Insights from agriculture have long suggested the use of facilitative legumes to ameliorate soil conditions (Bradshaw 1983, Wong 2003. More recent studies have shown mycorrhizal inoculation improves plant survival and growth (e.g., Requena et al 2001, Pineiro et al 2013 although in some systems it may be the presence of a mycorrhizal network (Simard and Durall 2004, Teste et al 2009, Booth and Hoeksema 2010, as opposed to the presence of certain mycorrhizas alone, that facilitates successful restoration.…”
Section: Restoring Species Composition Requires More Than Just Plantsmentioning
confidence: 99%
“…Ectomycorrhizal networks may increase survival of conspecific seedlings in a spatially structured fashion, disproportionately increasing their abundance near adult trees (Onguene and Kuyper 2002;Henkel 2003;McGuire 2007;Teste et al 2009;Booth and Hoeksema 2010) in a manner consistent with positive plant-soil feedbacks (reviewed by Bever et al 2012). In turn, the presence and strength of plant-soil feedback depends on the functional traits and taxonomic composition of the EM fungal community (e.g., Dickie et al 2002;O'Brien et al 2010;Kennedy et al 2012).…”
Section: Original Papermentioning
confidence: 99%
“…The respective (quartile) figures for herbaceous plants were 3%–7% (ECM) and 40%–49% (AM). The mycorrhizal mediation hypothesis has been tested several times with a focus on ECM plants and in most cases the data supported the hypothesis (e.g., Dickie, Guza, Krazewski, & Reich, 2004; Richard, Selosse, & Gardes, 2009; Teste et al., 2009; Moeller, Dickie, Peltzer, & Fukami, 2015) which appears to be due to ECM propagule limitation (Dickie et al., 2004; Dickie, Davis, & Carswell, 2012) . Despite our awareness that AM propagules decline in the forest compared to herbaceous systems (Fisher & Fulé, 2004), we know much less about the possibility that mycorrhizal mediation exists in temperate forests with regard to AM fungi.…”
Section: Introductionmentioning
confidence: 99%